THE INFLUENCE OF WORK MOTIVATION AND WORK COMMITMENT ON MADRASAH TEACHERS' LOYALTY - Moh. Sahal; Muhammad Khoiruddin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to describe the influence of work motivation and work commitment on the loyalty of teachers working in madrasahs. Employing a qualitative approach with library research as its primary research design, data were collected from relevant books, scientific journal articles, and academic sources. The collected data were then analyzed using Content Analysis to identify and interpret patterns and themes , complemented by triangulation to enhance credibility. The results indicate that teacher loyalty does not develop spontaneously but is simultaneously and significantly shaped by both work motivation and work commitment. Work motivation, consisting of intrinsic and extrinsic drives, encourages teachers to perform their duties with enthusiasm, discipline, and perseverance. Meanwhile, work commitment—encompassing affective, continuance, and normative dimensions—reflects teachers' emotional and moral attachment to the institution, driving them to comply with regulations and remain loyal despite various challenges. Within the madrasah context, these factors are deeply intertwined with spiritual values, sincerity, and the intention to regard teaching as an act of worship. Consequently, the relationship among work motivation, work commitment, and teacher loyalty is mutually reinforcing , collectively contributing to institutional stability, enhanced instructional quality, and a harmonious working environment. Based on these findings, it is highly recommended that madrasah management prioritize strategies to strengthen teacher motivation and commitment through inspirational leadership, fair reward systems, and the reinforcement of Islamic values.